2021
DOI: 10.1111/jdi.13575
|View full text |Cite
|
Sign up to set email alerts
|

Association between glycemic control and cardiovascular events in older Japanese adults with diabetes mellitus: An analysis of the Japanese medical administrative database

Abstract: Aims/Introduction The relationship between glycated hemoglobin (HbA1c) and cardiovascular events in older adults was investigated using a Japanese administrative medical database. Materials and Methods Anonymized medical data on patients with diabetes mellitus aged ≥65 years for the period from January 2010 to December 2019 were extracted from the EBM Provider database. The primary end‐point was a composite of cardiovascular events, whereas the other end‐points included severe hypoglycemia and fracture. The as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…Because the database contained data collected from approximately 20% of all large hospitals across Japan, the study would represent the general glycemic status in Japanese elderly persons with diabetes. HbA1c in the present study was 7.0%, which was similar to, but slightly higher than in that study 39 . Interestingly, SGLT2 inhibitors were more prescribed in the patients receiving LDL‐C‐lowering therapy than in patients not receiving it.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Because the database contained data collected from approximately 20% of all large hospitals across Japan, the study would represent the general glycemic status in Japanese elderly persons with diabetes. HbA1c in the present study was 7.0%, which was similar to, but slightly higher than in that study 39 . Interestingly, SGLT2 inhibitors were more prescribed in the patients receiving LDL‐C‐lowering therapy than in patients not receiving it.…”
Section: Discussionsupporting
confidence: 84%
“…The number of older adults with diabetes has been increasing in proportion to the overall aging of the Japanese population. A study based on the Japanese medical administrative database for the period from January 2010 to December 2019 reported that the mean HbA1c was 6.82% in 3,946 patients with type 2 diabetes mellitus aged ≥65 years under continuous physician‐supervised treatment 39 . Because the database contained data collected from approximately 20% of all large hospitals across Japan, the study would represent the general glycemic status in Japanese elderly persons with diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…However, a J-shaped relationship was observed between stroke incidence and HbA1c in the J-EDIT study, where an HbA1c level of 7.3–7.9% was correlated with the lowest risk 10 . Furthermore, a recent analysis of a Japanese administrative medical database revealed that older diabetic patients with poor glycemic control were at a higher risk of cardiovascular events, but patients with HbA1c levels < 7.2% showed no further risk reduction by decreasing HbA1c 11 . Therefore, tight glycemic control should be avoided to prevent macrovascular complications in older adults with diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…Although there are several causes of hypoglycemia, the majority of cases among patients with diabetes arise from use of glucose-lowering therapies, particularly insulins and sulfonylureas [2,3]. Severe hypoglycemia is a serious complication of diabetic therapy, associated with increased risk of mortality and morbidity [4][5][6][7][8] and significant socioeconomic costs, including the frequent requirement for emergency department visits and hospitalization [9].…”
Section: Introductionmentioning
confidence: 99%